Childhood sexual abuse: sibling perspectives - Wilson, Charlotte; Crabtree, Elaine; McElvaney, Rosaleen (My University, 2018)
Despite a recent focus highlighting the systemic impact of childhood sexual abuse (CSA), the needs of nonabused siblings have been largely overlooked. This interpretative phenomenological analysis study explored the lived experience of nonabused adult siblings of survivors of CSA. Semistructured interviews were undertaken with five adult siblings who were, or had been attending a support service. Emergent themes demonstrated the personal and relational impact of CSA on siblings which were captured across five domains: trying to make sense of it all, struggling to provide support, managing the impact on the wider family, feeling silenced and finding a voice, and rescripting the future. Participants struggled to make sense of their sibling’s experience, questioning their own memories of happy childhoods, often in the face of limited information about what happened. The impact of the sexual abuse not only affected the sibling relationship but was compounded by the distress of other family members, particularly parents. Participants reported feeling a lack of reciprocity in terms of their own support needs and described ongoing issues arising from the sexual abuse that they believed would likely continue for the rest of their lives. How siblings can be supported through psychoeducation and family therapy is discussed, both for their own needs and those of the entire family.
PUBLISHED
Keywords: Sexual abuse; Child abuse; Family issues and mediators; Vicarious trauma; Identities in Transformation; CSA; SIBLINGS